Dental Health Education and Recognition of Radiation Risk among Children of Foreign Workers in Malaysia - Ika Rachmawati; Dimar Pangestikasari; Syarifah Nova Amiza Zam (Universitas Malahayati Lampung, 2026)
ABSTRACT Introduction: Education and healthcare are two areas where foreign workers in Malaysia frequently encounter obstacles, particularly when it comes to their children. Health issues that can be avoided can result from a lack of awareness about mouth hygiene and the dangers of radiation exposure from dental imaging procedures. Children of migrant workers in Malaysia are being educated about radiation safety and the significance of good dental hygiene through community-based oral health education initiatives that have been applied worldwide. Purpose: The community of migrant workers' children was the target of this program, which sought to promote preventative measures and address oral health inequities. Research Methods: The program comprised interactive lectures, demonstrations of correct toothbrushing techniques, and educational sessions on the safe application of dental radiography. Participant comprehension was assessed via a written survey employing a pre- and post-intervention design, lacking a control group, to evaluate the educational program's influence on participants' understanding of dental health and the hazards associated with radiation exposure. Results: Illustrated a greater comprehension of radiation hazards and good behavioral modifications pertaining to maintaining tooth health. Conclusion: For vulnerable populations, interactive dental health education programs can be a useful strategy for enhancing both general and dental health outcomes. Keywords: Oral Health Education, Radiation Safety Awareness, Children Of Migrant Laborers